PERSONALIZED LEARNING THROUGH ARTIFICIAL INTELLIGENCE IN ENGLISH LANGUAGE EDUCATION - Hojiakbar Akhmadjonov, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract.  Artificial  Intelligence  (AI)  has  transformed  modern  education  by enabling personalized learning experiences that meet the diverse needs of individual students. In English language education, AI-powered technologies provide adaptive instruction,  instant  feedback,  personalized  learning  paths,  and  interactive  learning environments  that  improve  students'  language  proficiency  and  motivation.  Unlike traditional classroom instruction, where all learners often receive the same materials and pace  of instruction,  AI allows  educational  content  to be  tailored according  to students'  abilities,  learning  styles,  and  progress.  This  article  explores  the  role  of artificial  intelligence  in  personalized  English  language  learning,  discusses  its advantages  and  challenges,  and  highlights  practical  applications  of  AI  in  English language education.